Tracheopbronchopatia osteochondroplastica – a case presentation - Makuch, Marcelina; Szmygin-Milanowska, Katarzyna; Michnar, Marek; Palonka, Michał; Krusiński, Adam; Grzywa-Celińska, Anna (Journal of Education, Health and Sport, 2018)
Narrowing of the lower respiratory tract is a rare pathology. It may be associated with pathologies of the primary respiratory system or connective tissue diseases (systemic scleroderma, granulomatosis with polyangiitis, relapsing polychondritis). It can lead to non-specific clinical symptoms. We present an interesting case of a 52-year old patient with a history of several months’ dyspnea. Imaging tests revealed significant stenosis of the trachea and the left main bronchus. Tracheobronchopatia osteochondroplastica was diagnosed. Moreover, we carry out the differential diagnosis of the above pathology.